Frequency of cardioversions as an additional risk factor for stroke in atrial fibrillation - the FinCV-4 study - Jaakkola Samuli; Kiviniemi Tuomas O; Jaakkola Jussi; Pouru Jussi-Pekka; Nuotio Ilpo; Vasankari Tuija; Hartikainen Juha EK; Airaksinen KE Juhani (TAYLOR & FRANCIS LTD, 2022)
Background
Patients with atrial fibrillation (AF) are selected for oral anticoagulation based on individual patient characteristics. There is little information on how clinical AF burden associates with the risk of ischaemic stroke or systemic embolism (SSE). The aim of this study was to explore the association of the frequency of cardioversions (CV) as a measure of clinical AF burden on the long-term SSE risk, with a focus on patients at intermediate stroke risk based on CHA(2)DS(2)-VASc score. For these patients, additional SSE risk stratification by assessing CV frequency may aid in the decision on whether to initiate oral anticoagulation.
Methods
This retrospective analysis of FinCV Study from years 2003-2010 included 2074 patients who were not using any oral anticoagulation (long term or temporary) after CVs and undergoing a total of 6534 CVs for AF from emergency departments of three hospitals. Two study groups were formed: high CV frequency (mean interval between CVs <= 12 months and low frequency (>12 months).
Results
A total of 107 SSEs occurred during a mean follow-up of 5.4 years. The event rates per 100 patient-years were 1.82 and 0.67 in high versus low CV frequency groups, respectively. After adjustment for CHA(2)DS(2)-VASc score, CV frequency independently predicted SSE (HR, 2.87 [95% CI, 1.47 to 5.64]; p = .002) at 3 years. Competing risk analysis also identified CV frequency (sHR, 2.70 [95% CI, 1.38-5.31]; p = .004) as an independent predictor for SSE. In patients with CHA(2)DS(2)-VASc score 1 and low CV frequency, the SSE risk was only 0.08 per 100 patient-years.
Conclusions
Frequency of CVs for symptomatic AF episodes provides additional information on stroke risk in AF patients with CHA(2)DS(2)-VASc score 1.
Key messages
This retrospective study offers a unique opportunity to observe the natural course of AF patients with infrequent episodes of clinical arrhythmia when they were not using OAC (before introduction of CHA(2)DS(2)-VASc score).
Stroke or systemic embolism rate was very low (0.08 per 100 patient-years) in patients with one CHA(2)DS(2)-VASc point who visited the emergency room for cardioversion less than once a year.
Frequency of cardioversions can be used for additional risk stratification in patients at intermediate risk of stroke based on CHA(2)DS(2)-VASc score.